Short Communication: Plastic degradation by Coriolopsis byrsina, an identified white-rot, soil-borne mangrove fungal isolate from Surabaya, East Java, Indonesia - NENGAH DWIANITA KUSWYTASARI; ALFIA R KURNIAWATI; NUR HIDAYATUL ALAMI; ENNY ZULAIKA; MAYA SHOVITRI; KYU MIN OH; NI NYOMAN TRI PUSPANINGSIH; NI’MATUZAHROH NI’MATUZAHROH (Society for Indonesian Biodiversity, 2019)
Abstract. Kuswytasari ND, Kurniawati AR, Alami NH, Zulaika E, Shovitri M, Oh KM, Puspaningsih TP, Ni’matuzahroh. 2019. Plastic degradation by Coriolopsis byrsina, an identified white-rot, soil-borne mangrove fungal isolate from Surabaya, East Java, Indonesia. Biodiversitas 20: 867-871. The work deals with an important environmental issue, the disposal of plastic waste. The degradation of plastic by white-rot fungi of soil-borne mangrove isolate, T1P2, from Surabaya, East Java, Indonesia, was investigated using Minimal Salt Medium and the ability of the degradation was indicated as the amount of degradation efficiency. Analysis of the 18S rDNA sequence successfully identified the ligninolitic fungal isolated, T1P2, as Coriolopsis byrsina. The results have been revealed that C. byrsina have more potential to degrade plastic with maximum % DE was 22,7% for six weeks compared with the enzymatic plastic degradation reached 6,3% for two days. However, this study needs to do further investigation of extracellular enzyme that involved in degradation process.